Bioprocessos únicos e integrados na estabilização de resíduos de restaurante - Poncio, Anna Paula (2022)
Waste management is a major challenge within modern societies, fundamental for environmental sustainability and the improvement of life quality. The food sector has been one of the main sources of waste generation in recent years and restaurants stand out for the abundance of food waste that is generated, classified as solid organic waste (SOW). It is estimated that 931 million tons of food waste (FW) were generated in 2019, 26% of which came from the food service industry. When disposed of in the environment incorrectly, food waste generates problems such as nutrient leaching, emission of polluting gases and contamination, as it is considered a public health problem. This dissertation aimed to evaluate the effect of different stabilization bioprocesses on SOW generated in restaurants, regarding its physicochemical characteristics as well as the agronomic value of the final product. For this purpose, the research carried out aerobic composting treatments, direct vermicomposting and vermicomposting integrated with composting pretreatment and anaerobic treatments by means of anaerobic monodigestion (MonoDA) and anaerobic codigestion (CoDA). The composting process was executed for 100 days using closed compost bins. Three treatments were performed, all in triplicate, with different proportions in volume of FW and grass clippings as structuring agent. The performance of the process was evaluated in terms of temperature and mass and volume reductions, the organic compounds in terms of physicochemical and spectroscopic characteristics. Vermicomposting was conducted through six treatments, three of which with waste that had been pre-composted for 25 days (T4, T5 and T6), coming from the aforementioned composting treatments and three treatments with the same proportions, but with raw waste instead (T1, T2 and T3). At the end, the physicochemical and spectroscopic characteristics of the vermicomposts, number of eggs, young and adult earthworms were evaluated. The anaerobic assays utilized FW diluted with water for the MonoDA and dairy cattle wastewater for the CoDA, which were conducted for 60 days. Process performance was evaluated through biogas production potential, methane production potential, methane content in the biogas and physicochemical characteristics of the digestate. In some parameters of the composting result, an interference of the FW percentage was observed. Treatment T2, performed with the highest percentage of food, displayed the lowest exothermic index (2329.9 °C) when compared to the other treatments and the lowest values of pH, CTC and CTC:COT ratio. Main component analysis (MCA) revealed similarity between the compounds of T1 and T3 at 100 days of process and greater proximity to maturity parameters, whilst T2 exhibited the opposite trend. The direct vermicomposting and integrated vermicomposting processes, with pre-treatment in closed compost bins, showed similar results in relation to the adaptation and survival of the earthworms and regarding the spectroscopic analysis. When it comes to the physicochemical characteristics, the multivariate analysis allowed the research to conclude that only the treatment T6 was different from the others. Under the conditions studied, the quality of the vermicompost was influenced by the bioprocesses integration only in the proportion of 40% FW and 60% grass clippings (T6). In the anaerobic treatments, the best energy recovery condition occurred through CoDA, with methane content of 56.22%, biogas production in 0.642 L g-1 SVadd d -1 and methane production in 0.352 L CH4 g -1 SVadd d -1 ; however, the process showed signs of imbalance and acidification at the end of 60 days. The MonoDA produced less biogas and methane content, with acidification prior to CoDA. The analyzes allowed this study to conclude that the processes carried out are viable alternatives xii for the recycling of nutrients contained in the FW and for the generation of clean energy. On the other hand, the integration of processes did not engender additional advantages to vermicomposting.